Elizabeth Manning Hawthorne : a life in letters - Hawthorne, Elizabeth Manning, 1802-1883 (University of Alabama Press, 2006)
Cecile Anne de Rocher is Assistant Professor of English at Dalton State College in Georgia and a 2004 Governor's Teaching Fellow.